2019
DOI: 10.1007/s00018-019-03402-z
|View full text |Cite
|
Sign up to set email alerts
|

The one thousand and one chaperones of the NF-κB pathway

Abstract: The NF-B pathway represents a crucial signaling mechanism in sensing and integrating a multitude of environmental and intracellular stimuli and directing a coordinated response that from the cellular level may impact on the entire organism. A plethora of chaperone proteins works at multiple steps of the pathway, from membrane receptor activation to transcription factor binding to DNA. Indeed, chaperones are required to assist protein conformational changes, to assemble supramolecular complexes and to regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 204 publications
1
12
0
Order By: Relevance
“…Guo et al confirmed that Rg3 can inhibit the inflammatory macrophages infiltration and injury of induced by persistent hyperglycemia by up-regulating the expression of PPARg (Guo et al, 2018), and PPARg is the target of anti-diabetes, our study further confirmed Rg3 not only improve hyperglycemia complicated with AS, but also has a good effect on AS caused by dyslipidemia by regulating PPARg. Furthermore, Rg3 regulated PPARg/FAK pathway accompanied with the repression of inflammatory factors-NF-kB in our study, and in addition to FAK-mediated pro-inflammatory NF-kB in AS (Chen et al, 2018), IkB kinases (IKKs) activation which triggered by assembly of multiprotein complexes starting a cascade of protein phosphorylation, non-degradative ubiquitination, and higherorder oligomerization directly mediates NF-kB activation (Fusella et al, 2019); meanwhile, miRNAs may regulate the expression of adhesion molecules through NF-kB pathway, which directly controls their transcription (Zhong et al, 2018), thus prompting that we should further focus on the research to make clear how Rg3 inhibit NF-kB and related pathways in endothelial cell, and further verify our results by using endothelial specific PPARg deficient mice, so as to provide more basis for the application of Rg3 in AS.…”
Section: Discussionsupporting
confidence: 52%
“…Guo et al confirmed that Rg3 can inhibit the inflammatory macrophages infiltration and injury of induced by persistent hyperglycemia by up-regulating the expression of PPARg (Guo et al, 2018), and PPARg is the target of anti-diabetes, our study further confirmed Rg3 not only improve hyperglycemia complicated with AS, but also has a good effect on AS caused by dyslipidemia by regulating PPARg. Furthermore, Rg3 regulated PPARg/FAK pathway accompanied with the repression of inflammatory factors-NF-kB in our study, and in addition to FAK-mediated pro-inflammatory NF-kB in AS (Chen et al, 2018), IkB kinases (IKKs) activation which triggered by assembly of multiprotein complexes starting a cascade of protein phosphorylation, non-degradative ubiquitination, and higherorder oligomerization directly mediates NF-kB activation (Fusella et al, 2019); meanwhile, miRNAs may regulate the expression of adhesion molecules through NF-kB pathway, which directly controls their transcription (Zhong et al, 2018), thus prompting that we should further focus on the research to make clear how Rg3 inhibit NF-kB and related pathways in endothelial cell, and further verify our results by using endothelial specific PPARg deficient mice, so as to provide more basis for the application of Rg3 in AS.…”
Section: Discussionsupporting
confidence: 52%
“…A previous study had found that artificially oxidized oil could induce an inflammatory reaction of broilers, and the levels of IL-1β and TNF-α in serum were significantly increased ( Dong et al, 2020 ). At the same time, when a stressor invades, TLRs can recognize specific proteins on the surface of the stressor and activate the NF-κB signaling pathway through adaptor proteins such as MyD88 ( Fusella et al, 2020 ). NF-κB activated by Ikk is transported into the nucleus and induces the expression of a variety of proinflammatory factor genes to play a regulatory role in apoptosis ( Li et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NFкB family of transcription factors include NF-κB1 (p50), NF-κB2 (p52), RelA (p65), RelB and c-Rel, which homo- or heterodimerize to interact with specific DNA binding sites. Upon phosphorylation of the NFкB regulator IκB (inhibitor of NFкB) by IKK (IκB kinase) the NFкB protein is released from the inhibitory complex and translocates to the nucleus to regulate transcription ( 146 ).…”
Section: Transcription Factorsmentioning
confidence: 99%